Risks in the investment activity of Polish regions - Filipiak, Beata Zofia; Dylewski, Marek (Ryzyko w działalności inwestycyjnej regionów w Polsce, 2018)
Investment activities executed by regional authorities are exposed to high risk. The risk results from the very essence of investment projects implemented by regions in Poland and can be associated with the failure to meet the regional budget. The purpose of this study is to assess the size of the existing discrepancies between the planned and actually incurred investment expenditure and to find out if there are systematic changes in the level of these discrepancies i subsequent years. This goal was achieved through the presentation of the specific approach to risk measurement in the investment activities of local government units. The research was undertaken by regional self-government units. Empirical research has allowed us to answer three research questions: how great were the disparities between the planned and the actually incurred investment costs in the Polish regions in 2011-2015? Did systematic changes in the level of inconsistency between the planned and the actually incurred costs take place in the observed period? Was the rate of failure to meet investment plans correlated with the rate of failure to meet operational financial plans?
Financial Sciences. Nauki o Finansach, 2018, vol. 23, no. 4, s. 25-37
Keywords: local government; expenditure; infrastructure; financial risk